Increasing our knowledge of Brazilian bamboos: two new species of Chusquea subg. Rettbergia (Bambusoideae, Poaceae) - Mota, Aline Costa; Oliveira, Reyjane Patrícia De; Clark, Lynn G. (Phytotaxa, 2014)
Brazil includes a very high diversity of bamboos, but this diversity is far from completely known. We increase the list of Brazilian woody bamboos by describing two new species of Chusquea, which belong to subgenus Rettbergia. Chusquea ciliatifolia sp. nov. differs from other species of this subgenus by its mottled culms, distinctly ciliate margins of the foliage leaf blades and pilose synflorescences; and C. mirabilis sp. nov. by the presence of branches with sericeous girdles. Both C. ciliatifolia and C. mirabilis occur exclusively in the Atlantic Forest, from the states of Bahia and Minas Gerais, known only from five and three populations, respectively. Comments on morphology, taxonomic relationships, ecological aspects, and conservation status of these new species are provided.